THE EFFECTS OF STOCKING DENSITY ON CLOSED TRANSPORTATION SYSTEM OF JUARO FISH (Pangasius polyuranodon Blkr) - Saiful Muda’i; Niken Ayu Pamukas; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The objective of the research was to investigate the best stock of juaro fish on closed transportation system. The method used in this research was experimental method using Completely Randomized Design (RAL) of one factor 3 treatment levels and 3 replications, ie P1: density of juaro 8 fish/L, P2:density of juaro 10 fish/L and P3: density of juaro 12 fish/L. This research was conducted in June to July 2017 in the UPT Aquatic Aquaculture Technology Laboratory of Marine Fishery University of Riau. The result of this research was obtained by optimum stocking density the transportation of Juaro fish seeds with the addition of 20 g zeolite, 10 g of activated carbon and 4 g of salt which was transported for 8 hours was 8 fish/L. It is characterized by a survival rate (SR) of 58.33%, temperature 280C, DO 2.23 mg/L, CO2 0.87 mg/L, pH 7, NH3 0.23 mg/L and post-transport cortisol blood 179,406 nmol/L. Keywords : Stock Density, Pangasius polyuranodon, Closed Transportation System,